Review of Levan polysaccharide: From a century of past experiences to future prospects - TOKSOY ÖNER, EBRU (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Levan is a fascinating beta-(2,6)-linked fructose polymer with an unusual,combination of properties characterized in this review. In nature, levan is synthesized from sucrose by a wide range of microorganisms and a few plant species. Bacterial levans often have molecular weights over 500,000 Da, are commonly branched, and form compact nanospheres offering a broad spectrum of applications. The most relevant genetic, biochemical and structural aspects of the biosynthetic enzyme levansucrase are detailed. Optimization of parameters for levan production by intact bacteria and by the isolated enzyme is surveyed. The diversity of current and potential applications of levan is illustrated by a discussion of uses ranging from personal care and aquaculture to the medical and food industries. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Levan; Polysaccharide; Fructan; Levansucrase; ACETOBACTER-DIAZOTROPHICUS SRT4; ROHITA HAMILTON JUVENILES; BACILLUS-SUBTILIS NATTO; NOXIOUS GAS EMISSION; SYRINGAE PV. TOMATO; ZYMOMONAS-MOBILIS; MICROBIAL LEVAN; STRUCTURAL-ANALYSIS; MOLECULAR-WEIGHT; STREPTOCOCCUS-SALIVARIUS